Jane Fonda at Watkins' Home re Campaign for Economic Democracy Fundraiser - Watkins, Howard::::::::: (1982)
Rose Watkins talking with Jane Fonda re signing book about Eleanor Roosevelt and 3 Jane Fonda Workout books